A bigger bang for the public buck: A non-parametric efficiency analysis of state highway infrastructure investment. Issue 3 (3rd September 2018) - Chen, Can
Abstract : Purpose: It is well known that public infrastructure, particularly the transportation infrastructure sector, is notorious for low efficiency, spending waste and corruption. Achieving the efficiency of public infrastructure investment is a crucial element to improve the current deteriorating condition of American transportation infrastructure system. The paper aims to discuss these issues. Design/methodology/approach: This research utilizes an input-oriented, variable return to scale non-parametric data envelopment analysis to estimate the relative cost efficiency of highway infrastructure investment among the 48 American continental states from 1995 to 2009. Findings: The empirical results reveal that there is a large efficiency variation among state highway infrastructure systems. Practical implications: In addition, state governments on average reach 95.8 percent of the efficiency of their best practice peers in terms of providing quality highway infrastructure outcomes.